2022
DOI: 10.1002/jemt.24235
|View full text |Cite
|
Sign up to set email alerts
|

Tuning structural properties, morphology and magnetic characteristics of nanostructured Ni‐Co‐Fe/ITO ternary alloys by galvanostatic pretreatment process

Abstract: In this research, the structural properties, surface morphology, and magnetic characteristics of nanostructured ternary ferromagnetic alloys grown by a cost‐effective and effortless two‐step electrochemical deposition method on indium tin oxide (ITO) substrates with and without a galvanostatic pretreatment process (GPP) were examined. The GPP was applied at various pretreatment current densities (PCDs) such as −10, −20, and − 30 mA/cm2. The effect of the PCD on the Ni, Co, and Fe contents is found to be insign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 79 publications
3
9
0
Order By: Relevance
“…This type of IP M-H loop has also been reported in recent studies for binary and ternary magnetic materials produced by the ECD and mechanical synthesis methods. 16,17,21,22,57,58 Table 2 also demonstrates that lowering the electrolyte pH causes an increase in the coercive field. The coercive field increases slightly from 29.4 Oe to 33.2 Oe as the pH of the electrolyte decreases from 4.7 to 3.9, and then increases sharply from 33.2 Oe to 41.3 Oe when the pH of the electrolyte drops from 3.9 to 3.2.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…This type of IP M-H loop has also been reported in recent studies for binary and ternary magnetic materials produced by the ECD and mechanical synthesis methods. 16,17,21,22,57,58 Table 2 also demonstrates that lowering the electrolyte pH causes an increase in the coercive field. The coercive field increases slightly from 29.4 Oe to 33.2 Oe as the pH of the electrolyte decreases from 4.7 to 3.9, and then increases sharply from 33.2 Oe to 41.3 Oe when the pH of the electrolyte drops from 3.9 to 3.2.…”
Section: Resultsmentioning
confidence: 91%
“…Other components are due the ITO glass and activated carbon. 21,28,33 The composition of the resultant deposits is illustrated in Figure 2. It is found that the deposits manufactured at high pH values of 4.7 and 3.9 contain very close Fe (12.4-12.8 at.%), Co (28.7-29.7 at.%) and Ni (57.9-58.5 at.%) contents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The statistical parameters, namely, RMS roughness ( S q ), skewness ( S sk ), kurtosis ( S ku ), and arithmetic mean height values ( S a ), were calculated using eqs –, respectively. The equations are obtained from ISO 25178 data. …”
Section: Resultsmentioning
confidence: 99%